Semi-automatic Slicer - Khaidir, Muhammad Alif Najmi; Musa, Mursyid; Wan Ahmad Rizalle, Wan Haikal Fitri; Mat Zian @ Mat Zin, Ahmad Faiz (Multidisciplinary Applied Research and Innovation, 2022)
Semi-automatic Slicer is a machine that can slice banana, tapioca and yam into a chips product. This machine aims to provide a better solution for the Small and Medium Industry in producing chips from banana, tapioca and yam. This machine can enhance the slicing rate to be faster thus improve the productivity rate. On top of that, it only requires a single person to operate the machine. This machine is user friendly. The main objective for this project is to design and fabricate a semi-automatic multipurpose slicer and to perform parametric analysis test to the slicer functionality and performance. This machine can slice banana, tapioca and yam by only using a single machine. The user is only required to insert the raw material into the machine feeder for making the product.  The machine development process involves machine design, material selection, metal works fabrication, assembly, testing, and re-modification to achieve a fully functional machine. The machine was tested according to project objectives, and the results were compared to a manual multipurpose slicer. The machine is capable of lower the production time taken to slice banana, yam and tapioca up to 66% faster.